2018
DOI: 10.20307/nps.2018.24.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Estragole Exhibits Anti-inflammatory Activity with the Regulation of NF-κB and Nrf-2 Signaling Pathways in LPS-induced RAW 264.7 cells

Abstract: − Estragole is a naturally occurring phenylpropanoid obtained from essential oils found in a broad diversity of plants. Although the phenylpropanoids show many biological activities, clear regulation of the inflammatory signaling pathways has not yet been determined. Here, we scrutinized the anti-inflammatory effect of estragole. The anti-inflammatory effect of estragole was determined through the inhibitory mechanisms of inducible nitric oxide synthase (iNOS), cyclooxygenase (COX-2), nuclear factor kappa B (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Nitric oxide is synthesized during immune and inflammatory responses of the host against infectious agents. Nitric oxide is used as a toxin for the self-defense of the host or acts as an immunoregulatory mediator that participates in both innate and adaptive immune responses [33,34]. Our results also showed that the synthesis of NO was slightly stimulated by treatment with prednisolone (PDS) and 5-aminosalicylic acid (5-ASA), even though they were used as anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 63%
“…Nitric oxide is synthesized during immune and inflammatory responses of the host against infectious agents. Nitric oxide is used as a toxin for the self-defense of the host or acts as an immunoregulatory mediator that participates in both innate and adaptive immune responses [33,34]. Our results also showed that the synthesis of NO was slightly stimulated by treatment with prednisolone (PDS) and 5-aminosalicylic acid (5-ASA), even though they were used as anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 63%
“…The site in which most dehydrocostus lactone accumulated was the lung. A recent study revealed that dehydrocostus lactone was effective in the attenuation of LPS-induced acute lung injury in mice via the inhibition of nuclear factor-κB [ 29 , 30 ]. Thus, our present results may support those of this previous study.…”
Section: Resultsmentioning
confidence: 99%
“…The analgesic effect of basil has been attributed to its compounds. Cineole, geraniol, flavonoids, and estragole have anti-inflammatory properties [45][46][47][48][49]. Extract of Table 2.…”
Section: Discussionmentioning
confidence: 99%